Identifikasi Potensi Bahaya Gelombang Seismik Berdasarkan Parameter Dinamis Tanah di Kecamatan Selebar - Nirvana, Aura; Mase, Lindung Zalbuin; Amri, Khairul; Misliniyati, Rena; Hardiansyah, Hardiansyah (Universitas Sultan Ageng Tirtayasa, 2025)
The Selebar District in Bengkulu City has a high level of earthquake vulnerability due to its location near the Indo-Australian and Eurasian plate subduction zone. This study began with a microtremor survey and earthquake modelling to analyse the seismic response of the soil. Modelling was conducted using the non-linear dynamic Pressure Dependent Hyperbolic (PDH) approach. This method models soil behaviour by considering changes in stiffness and damping due to variations in pressure and strain during an earthquake, thereby providing a more realistic representation of field conditions. The response analysis was conducted in one dimension and produced soil acceleration parameters, with Peak Ground Acceleration (PGA) values ranging from 0.47g to 0.75g. These results indicate a high earthquake potential in the study area. The acceleration spectrum of the input waves increased gradually until it reached its peak at a period of 0.2 seconds, covering the classification range of buildings from low to high. These findings provide essential input for earthquake-resistant infrastructure planning and the formulation of risk mitigation strategies in earthquake-prone areas, such as the Selebar District in Bengkulu City.